MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI MEDIA BUSY BOOK KELOMPOK A TK WACHID HASYIM 2 SURABAYA - SANTRI, BINA RAS (MOTORIC, 2025)
ABSTRACT This study aimed to determine the success of using video production to improve students' English speaking skills. The video had a different topic for each meeting. It used descriptive qualitative. The observations were conducted in 3 meetings. The research subjects were 19 students, consisting of 12 women and 7 men. The teaching aids were Google Meet and Edmodo. The results of the study showed that the usage of Edmodo was easily accessible, that is, you can use a PC, laptop and smartphone, and even Edmodo software was available on the Playstore. Then, Edmodo had a feature to create small groups. It was to avoid students' lies about uploading their assignments. However, Edmodo did not have a video conferencing feature, so one of the solutions was to use Google Meet. Furthermore, the implementation of video production could increase their confidence to speak English and they could even improve their video editing skills or knowledge.